1998
DOI: 10.1097/00005373-199806000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Improved Success in Nonoperative Management of Blunt Splenic Injuries

Abstract: Aggressive surveillance for and embolization of posttraumatic splenic artery pseudoaneurysms improved the rate of successful nonoperative management of blunt splenic trauma to 61%, with a nonoperative failure rate of only 6%. In comparison with our previous work, this reduction in failure of nonoperative management is a significant improvement (p < 0.03).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
214
2
9

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(231 citation statements)
references
References 12 publications
6
214
2
9
Order By: Relevance
“…Only 9.8% of patients in NOM and 8% in SAE, had a secondary splenectomy despite a high median ISS at 18.5 and the absence of a clearly defined protocol. This could argue in favor of SAE which seems to be more effective in cases of high-grade spleen injury, large hemoperitoneum, or associated vascular lesions (2,(6)(7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…Only 9.8% of patients in NOM and 8% in SAE, had a secondary splenectomy despite a high median ISS at 18.5 and the absence of a clearly defined protocol. This could argue in favor of SAE which seems to be more effective in cases of high-grade spleen injury, large hemoperitoneum, or associated vascular lesions (2,(6)(7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…Distal embolisation is often used for the treatment of focal vascular injuries such as pseudoaneurysms or arteriovenous fistulae [4,23]. Subsequent bleeding may occur because some vascular injuries are initially not detected at angiography or CT due to vasospasm [4,23].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent bleeding may occur because some vascular injuries are initially not detected at angiography or CT due to vasospasm [4,23]. However, a recent meta-analysis found that the only difference in short-term outcomes between the two techniques was a higher rate of splenic infarcts after distal embolisation [10].…”
Section: Discussionmentioning
confidence: 99%
“…Previously published papers describing these delayed events are almost all limited to splenic pseudoaneurysm. Davis et al 5. and Weinberg et al 6.…”
Section: Discussionmentioning
confidence: 98%
“…Some reports5, 6 have described the incidence and timing of splenic pseudoaneurysm formation, but there is no global consensus for repetitive imaging with computed tomography (CT), especially for injuries classified as low grade on the Trauma Organ Injury Scale of the American Association for the Surgery of Trauma (AAST), and there are no recommendations for the appropriate duration of hospital admission 7, 8…”
Section: Aimmentioning
confidence: 99%